A game-theoretic analysis of the impact of differential leadership on employee silence behavior in family enterprises - Lu, Jie; Chen, Yanxia; Xu, Yitian; Zhu, Yuqing (Frontiers in Physics, 2023)
The increasing uncertainty in the socio-economic landscape has heightened management's interest in and expectations for employees' opinions and suggestions. Concurrently, employee silence behavior is pervasive in today's corporate world, prompting widespread academic attention.This study employs the dynamic evolutionary game approach to further examine the impact of differential leadership on employee silence of both insiders and outsiders and underlying mechanisms, with a focus on the Chinese socio-economic context. The research findings reveal that both insiders and outsiders may exhibit non-silent behaviors to gain their leaders' attention and favor, ultimately achieving and sustaining benefit-seeking. Psychological empowerment and out-group preference emerge as key drivers of non-silent behaviors for internal and external employees, respectively.Based on the theories of psychology and social network, this research enriches the theory system of differential leadership behavior evolution and makes up for the deficiency of management in depicting the dynamic process of differential leadership behavior evolution, it provides a theoretical basis for grasping the evolution of differential leadership behavior and its rules of action. The investigation not only supplements and broadens the scope of relevant empirical research but also offers a theoretical foundation for analyzing and comprehending the evolution of differential leadership behavior and its consequences.